In Search of an Islamic Leader: Malay Perceptions of Ibn Sa’ūd Triumph and the Domination of the Waḥḥābīs in Saudi Arabia - Othman, Mohammad Redzuan (Studia Islamika, 2004)
Since becoming Muslim, the Malays have highly revered Hijaz and its 'ulama', and have seen them as a source of religious and political authority when the need for an authoritative decision arises. Even though historically Hijaz was exceptionally meaningful to the Malays, even for elucidating political questions, in Malaya there was no indication that the people were concerned with doctrinal or political developments with regard to the rise of Ibn Sa'ud's family and the early domination of the Wahhabis in the region, until the outbreak of the rivalry between Sharif Husayn and 'Abd al-Aziz Ibn Sa'ud after Worid War I.DOI: 10.15408/sdi.v11i2.602